COMPARATIVE EVALUATION OF ADHESIVE ABILITY OF MICROORGANISMS TO THERMOPLASTIC AND ACRYLIC BASE POLYMERS FOR REMOVABLE DENTAL PROSTHESES POLISHED WITH DIFFERENT PASTES - V.F. Makeyev; Ya.R. Hunovskyi (Український стоматологічний альманах, 2022)
The ability of microorganisms to penetrate into the thickness of the material directly depends on the surface quality and structure of the material. In order to counteract the adhesion and colonization of microorganisms, it is essential to obtain the smoothest possible surface of the prosthetic structure with low values of roughness and free surface energy. Non-compliance with the technique of manufacturing removable orthopedic structures with the formation of roughness, pores, and lack of proper care for the prosthesis promotes the adhesion of microorganisms and their penetration into the base of the dental prosthesis.